The Nexus between Islam and Development: A Review and Bibliometric Analytics - Nurus Shalihin (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to map bibliometric information related to the topic of Islamic relations and development, critically classify topics related to Islam's position in development, and the instruments that Islam offers for the development agenda. To that end, the study used a bibliometric approach and analyzed 273 articles from the Scopus database. To top it off, the study also used a systematic literature review (SLR) method to classify issues in 54 articles related to Islam and development. The findings of this study confirm that the topic of Islam and development in international journals showed an increase in the period 2012-2016, and the studies of Timur Kuran and Hossein Askari showed a reasonably high impact on the development of studies related to Islam and development